Fingerprint biometric voting machine using internet of things - Zakiah Mohd Yusoff; Yusradini Yusnoor; Arni Munira Markom; Siti Aminah Nordin; Nurlaila Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Free elections are one of democracy's principles. Elections will be used to choose the representatives of the people. It is underlined on how important it is to organize free, fair, and secret elections. Traditionally, voting used to be conducted by stamping on paper, then placing it in a ballot box with the chosen candidate. Each vote in every ballot box must be counted separately, and the votes for each contender must then be added up to determine which candidate had the most votes. Everything was done manually, it will take longer to announce the winner. Numerous errors are being made, but they will not change the outcome. In this study, a significant system that stops electoral malpractices and expedites the voting process will propose. The controller utilized in this project is the Arduino Uno. The user is authenticated using a fingerprint. Everybody's fingerprints differ from one another. The device is programmed using the Arduino IDE, and the ballot card is displayed, and the results are stored in the cloud. Only a registered voter may cast a vote, and the system alerts users to any fraud. This project protects citizens' freedom to vote and ensures an impartial election.